A new magnetic nanocomposite for selective detection and removal of trace copper ions from water. Issue 3 (1st December 2014) - Qiu, Xun; Li, Najun; Yang, Shun; Chen, Dongyun; Xu, Qingfeng; Li, Hua; Lu, Jianmei
Abstract : A new core–shell structured magnetic nanocomposite (SDMA) was successfully prepared for simultaneous detection and removal of trace Cu 2+ . In this facile strategy, the new nanocomposites could detect and adsorb trace Cu 2+ from water with high capacity and good removal efficiency. Abstract : A core–shell structured, magnetic nanocomposite (SDMA) modified by a new organic fluorescent probe and selective chelating groups was prepared for simultaneous detection and removal of low Cu 2+ concentrations. A series of experiments was designed to detect and adsorb copper ions in aqueous solution via SDMA. Results showed that SDMA could detect Cu 2+ from copper ion solution qualitatively and quantifiably with a certain degree of selectivity, and remove Cu 2+ with a respectable removal efficiency of about 80%. In comparative adsorption experiments, the adsorption capacity of SDMA was significantly higher than that of another two common magnetic nanoadsorbents (Fe3 O4 @mSiO2 –SH and Fe3 O4 @mSiO2 –NH2 ). The adsorption behavior of SDMA was studied through equilibrium and kinetic experiments. The adsorption isotherm was perfectly fitted via the Freundlich model and the pseudo-second-order model could fit the kinetic adsorption. Moreover, the SDMA could reach the adsorption equilibrium in only 20 min, which showed a fast kinetic adsorption to Cu 2+ . Prepared SDMA can be an effective and potential nanoadsorbent for detecting and removing copper ions from wastewater.